The motivated appeal to hypocrisy: the relation of motivational threats to message rejection - Pillow, David R.; Hale, Willie J.; Kohler, Janelle; Mills, Stephanie; Soler, Jasmine (Frontiers in Psychology, 2023)
Few studies have focused on the conditions in which individuals perceive hypocrisy in others.The current study introduces and tests the Motivated Appeal to Hypocrisy (MAtH) hypothesis. This hypothesis examines core social psychological motivational threats and asks (a) whether these are related to the accounts of individuals in charging others with hypocrisy, and (b) whether these perceptions of hypocrisy are associated with reductions in the persuasiveness of persons targeted as hypocrites. Study 1 (𝑁 = 201) was based on qualitative coding of stories and revealed that all five of Fiske's ( 2004) core social motives are involved in participants' stories of hypocrisy. Study 2 (𝑁 = 237) used a multilevel correlational approach and demonstrated that violations of core social motives significantly predict perceptions of hypocrisy and the rejection of a person's message or advice. The relation between social motive violations and message rejection was mediated by perceptions of hypocrisy.